Quantitative assessment of the switchability of generic products - Karalis, Vangelis; Bialer, Meir; Macheras, Panos (EUROPEAN JOURNAL OF PHARMACEUTICAL SCIENCES, 2013)
Generics are usually considered to exhibit comparable in vivo properties in terms of efficacy and safety and for this reason are intended to be interchangeable with the reference product. The aim of this study is to provide a quantitative picture of the switchability problem between two generics and to introduce the concept of conditional probability of bioequivalence (BE) acceptance. Monte Carlo simulations were performed to examine all possible relationships between the tested products. Four types of percent BE acceptances are defined and evaluated: (a) % BA1, when generic T-1 is compared to the R product, (b) % BA2, in cases of comparison of generic T-2 with the R product, (c) % BA21, when generic T-2 is compared to another generic T-1, and finally (d) % BA21C which is the conditional probability of percent bioequivalence acceptance of generic T(2)versus another generic T-1 given that both T-1 and T-2 are declared bioequivalent to the same R formulation. The simulations were expanded to study concomitantly the performance of T-1 and T-2 when compared to the same R formulation. In each case, the 2 x 2 cross-over design was used and evaluation of BE was based on the classic BE limits (0.80-1.25) and the stricter BE limits (0.90-1.11) for narrow therapeutic index (NTI) drugs. A number of 24 and 48 subjects were assumed to participate in the simulated trials, while the coefficient of variation for the within-subject variability (CVw) was 20% and 40%. A number 40,000 BE trials were simulated under each condition. The T-1/R and T-2/R ratios ranged from 0.80 to 1.25 using a step of 0.05. Even though two generics (T-1 and T-2) can be declared bioequivalent to the same R product, this does not ensure that they are always mutually bioequivalent. On the contrary, two generic products which differ substantially from the R product can still have a high probability to be truly interchangeable. The two generics (T-1 and T-2) can be switched from one to another when the T-1/R and T-2/R ratios are close to the same value, the CVw of the drug is low, and each BE study of T-1-R and T-2-R was conducted using a relatively large number of subjects. In the same context, two generic NTI drugs which differ more than 10% from the R product can still be declared bioequivalent to one another depending on the relative T-1/R and T-2/R ratios. Switchability between generics assessed at the 0.90-1.11 interval is safer, but not always ensured. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: bioequivalence; Conditional probability; Generics; Narrow therapeutic index drugs; pharmacokinetic simulations; Switchability